Excesso de confiança, ancoragem e conhecimento financeiro. O consumo das aplicações financeiras. - Cruz, Ricardo Chagas (2017)
The use of heuristics to support the rational analysis of economic agents when making decisions regarding gains and losses in the decision-making process in finance, from the 70's began to be questioned by scholars of Experimental Economics and Psychology generating A theoretical framework today called Behavioral Finance. With the contributions of Daniel Kahneman and Amos Tversky, Nobel Laureates in Economics (2002), the studies have taken a considerable boost in the finances of international and national markets that seek to understand how the investor comes to live with the uncertainties inherent in the process of Financial choice. This work sought to identify the relation of the heuristics of overconfidence and anchorage, when related to the level of knowledge of the investors in the consumption of financial investments when the investors become surplus. Decision making in the consumption of financial assets is permeated by uncertainties and risks of the most diverse nature, and has been studied since the 1950s, but it was in the 20th century that heuristics were considered as references capable of impacting the consumption decision of a Financial product. Through a quantitative research in class A and B - potential social layers of financial investments, we sought to investigate whether knowledge can impact the decision to choose a financial application.